Deficiency in the mRNA export mediator Gle1 impairs Schwann cell development in the zebrafish embryo. (13th May 2016) - Seytanoglu, A.; Alsomali, N.I.; Valori, C.F.; McGown, A.; Kim, H.R.; Ning, K.; Ramesh, T.; Sharrack, B.; Wood, J.D.; Azzouz, M.
Highlights: Impact of gle1 depletion on zebrafish development. Role of RNA-binding protein gle1 in motor neuron and Schwann cell development. Schwann cell may have a role in gle1-linked LCCS1pathology. Abstract: GLE1 mutations cause lethal congenital contracture syndrome 1 (LCCS1), a severe autosomal recessive fetal motor neuron disease, and more recently have been associated with amyotrophic lateral sclerosis (ALS). The gene encodes a highly conserved protein with an essential role in mRNA export. The mechanism linking Gle1 function to motor neuron degeneration in humans has not been elucidated, but increasing evidence implicates abnormal RNA processing as a key event in the pathogenesis of several motor neuron diseases. Homozygous gle1 −/− mutant zebrafish display various aspects of LCCS, showing severe developmental abnormalities including motor neuron arborization defects and embryonic lethality. A previous gene expression study on spinal cord from LCCS fetuses indicated that oligodendrocyte dysfunction may be an important factor in LCCS. We therefore set out to investigate the development of myelinating glia in gle1 −/− mutant zebrafish embryos. While expression of myelin basic protein ( mbp ) in hindbrain oligodendrocytes appeared relatively normal, our studies revealed a prominent defect in Schwann cell precursor proliferation and differentiation in the posterior lateral line nerve. Other genes mutated in LCCS have important roles in Schwann cell development, thereby suggesting that Schwann cell deficits may be a common factor in LCCS pathogenesis. These findings illustrate the potential importance of glial cells such as myelinating Schwann cells in motor neuron diseases linked to RNA processing defects.